2007
DOI: 10.1111/j.1468-2370.2007.00206.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of acquisitions on firm performance: A review of the evidence

Abstract: This paper presents a review of empirical research on the impact of acquisitions on firm performance. The evidence suggests that, in the short run, acquisitions have at best an insignificant impact on shareholder wealth. Long-run performance analysis reveals overwhelmingly negative returns, while the evidence using accounting performance measures is mixed. The review also examines the impact of bid characteristics on performance. The acquisition of hostile targets, transactions that are paid for with cash and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
166
4
7

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(186 citation statements)
references
References 116 publications
(231 reference statements)
9
166
4
7
Order By: Relevance
“…While Bruner (2002;2005) talks about 30% of deals failing, Jansen estimates 50%-75%. Overall, the majority of empirical literature on bidder performance in acquisitions has failed to provide consistent evidence for increased shareholder wealth (Tuch and O'Sullivan 2007). After reviewing the M&A literature focusing on merger policy in the US in great detail Mueller (1997) concludes: "It is possible, judging from the available evidence on the effects of mergers, that the US economy would be as or even more efficient today, if there had been no mergers over the last 50 years.…”
Section: ---------------------------------Insert Figure 1 About Here mentioning
confidence: 99%
See 2 more Smart Citations
“…While Bruner (2002;2005) talks about 30% of deals failing, Jansen estimates 50%-75%. Overall, the majority of empirical literature on bidder performance in acquisitions has failed to provide consistent evidence for increased shareholder wealth (Tuch and O'Sullivan 2007). After reviewing the M&A literature focusing on merger policy in the US in great detail Mueller (1997) concludes: "It is possible, judging from the available evidence on the effects of mergers, that the US economy would be as or even more efficient today, if there had been no mergers over the last 50 years.…”
Section: ---------------------------------Insert Figure 1 About Here mentioning
confidence: 99%
“…In developing our working hypothesis, we follow Tuch and O'Sullivan (2007), who conclude after a review of the literature on M&A and performance that there is some support for a positive effect on wealth creation in business related acquisitions:…”
Section: Business Relatednessmentioning
confidence: 99%
See 1 more Smart Citation
“…But there still is no agreement on the performance of the acquirer. Quite a few scholars, for example, Conn (1985) and Jarrel et al (1988) state that the acquirer usually shows positive performance after implementing the merger and acquisition, but, based on the research of Tuch and O'Sullivan (2007), the bad performance of the acquirer would not show for a long time so short-term studies may be misleading. Of 44 studies analysed by Bruner (2002), he concluded that acquiring firms have negative returns and targets are have positive returns.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this vein, we find very few review papers referring to cross-border acquisitions for various reasons, namely global and regional perspectives (Hopkins, 1999), stylized reviews on theoretical foundations (Chapman, 2003;Shimizu, Hitt, Vaidyanath, & Pisano, 2004), and post-merger integration issues (Öberg & Tarba, 2013). On the other hand, we also come across studies reviewing the M&A stream largely through accounting and finance lens (e.g., Martynova & Renneboog, 2008a;Tuch & O'Sullivan, 2007), and bibliometric papers (e.g., Ferreira, Santos, de Almeida, & Reis, 2014;Reddy, 2015b). Albeit, we propose that a comprehensive review of factors affecting cross-border investments and acquisitions is missing in the literature.…”
Section: Introductionmentioning
confidence: 99%